Retóricas sobre educação physica, sport e exercício físico no Jornal Minas Geraes entre 1913 e 1916 - Yuri Vitor Guimaraes Vieira (2013)
The present work aims to analyze some aspects related to body education which were published in the newspaper Minas Geraes between 1913 and 1916. In this publications the expressions Educação Physica, exercício físico and sport were frequently used. Given that in many of this publications it was possible to find a group of prescriptions which aimed peoples body education, I formulated and worked on the hypothesis that there was a moral investment that I denominated educação do corpo. Through this research, I tried to point out that this newspaper highlighted a transitional process which mixed new trends on body education and reassured old bodily practices in use in that period. It was possible to observe that there were three different prospects related to the moral aspect presented in these articles. The first, is revealed through the analyses of the papers of the priest Francisco Ozamis, in which it is possible to see how he, using the tradition of the Christian doctrine, found the basis to elaborate his recommendations about the so called Educação Physica. In the second, the medical rhetoric create a group of prescriptions about physical activity based on specialized orientation to the activities. In the writings of physician Ernest Monin, this recommendations were directed to the practice of physic activity and to feeding with the aim of inducing specific habits and behaviors in the individuals. On the other hand, in the work of the physician Theophilo Torres the moral aspect seems to be related basically to the international debate that happened that time in which seemed to exist a dispute regarding the body education model which should prevail. Finally, in the third prospect, the moral aspect seems to be aggregated to a transitional process regarding the bodily practices that existed in England and other countries throughout the 18th, 19th and 20th centuries. In this process, it is possible to see that there was a gradual disruption with the past and that new bodily practices based on the concept of bodys discipline and reinvigoration were established. All in all, I tried to highlight in the final considerations of the present work, that the understanding of the experiences dimension can be lead the researcher, who intends to investigate the bodily practices that existed in the past, to find more interesting findings than the use of the current concepts to understand the past.